Fused Systems Based on 2‐Aminopyrimidines: Synthesis Combining Deprotolithiation‐in situ Zincation with N‐Arylation Reactions and Biological Properties. Issue 39 (20th October 2017) - Hedidi, Madani; Maillard, Julien; Erb, William; Lassagne, Frédéric; Halauko, Yury S.; Ivashkevich, Oleg A.; Matulis, Vadim E.; Roisnel, Thierry; Dorcet, Vincent; Hamzé, Monzer; Fajloun, Ziad; Baratte, Blandine; et al.
Abstract : Various aromatic ketones were first functionalized next to the carbonyl function by deprotolithiation in the presence of a zinc salt followed by iodolysis. The outcome of the reactions was analyzed, and in particular their regioselectivity in the light of the calculated p K a values. Various halogenated ketones were next involved in copper‐catalyzed twofold C–N bond formation to obtain fused systems based on 2‐aminopyrimidines. Besides a potential antibacterial effect, 2‐aminobenzothiopyrano[4, 3, 2‐ de ]quinazoline was shown to inhibit PIM1 (IC50 : 0.61 µm ) and CDK2/cyclin A (IC50 : 2.0 µm ) kinases. Abstract : Aromatic ketones were functionalized by deprotolithiation in the presence of zinc salt followed by iodolysis. Reactions were analyzed relative to calculated p K a s. Copper‐catalyzed C–N bond formation with iodo derivatives gave fused systems based on 2‐aminopyrimidines. 2‐Aminobenzothiopyrano[4, 3, 2‐ de ]quinazoline has antibacterial effect, and inhibits PIM1 (IC50 0.61 µm ) and CDK2/cyclin A (IC50 2.0 µm ) kinases.